THE CONTRAST BETWEEN RURAL HEALTH SERVICES IN BIHAR AND KERALA - Kumari, Neetu (International Journal of Research -GRANTHAALAYAH, 2025)
This article evaluates the rural healthcare systems of Bihar and Kerala, two states of India at opposite ends of the health index, as per the report of Niti Aayog (2021). This article presents a comparative assessment of the rural healthcare systems of these two states of India. Bihar is at the bottom, and Kerala ranks the highest in the health index. This study examines the availability of health centres, building positions, the number of health workers (ANM), doctors, pharmacists, radiographers, laboratory technicians, and nursing staff at different levels of the rural healthcare system in Bihar and Kerala. This study analyses the number of required, sanctioned, in-place, and vacant posts for medical personnel such as medical workers, doctors, specialists, radiographers, pharmacists, laboratory technicians, and nursing staff. This paper also highlights the shortage of these medical personnel at different levels of the rural healthcare system. The comparison also considers the national context, focusing on the disparities and challenges associated with the rural healthcare system in India. This article basically attempts to make a comparative analysis associated with the shortfall of infrastructure and manpower.